Analisis Rata-rata PM2.5 Di Surabaya Raya Tahun 2024–2025 terhadap Baku Mutu Nasional dalam Perspektif Kesehatan Masyarakat - Shaila Rizka Annabila; Aditya Pawitra Sukma; Khuliyah Candraning Diyanah (Universitas Pahlawan Tuanku Tambusai, 2026)
PM2.5 is one of the key contributors to ambient air pollution, which poses a critical environmental problem in urban areas such as the Greater Surabaya Region, characterized by high levels of transportation and industrial activity. PM2.5 can penetrate the lower respiratory tract, thereby increasing the risk of cardiovascular and respiratory disorders as well as noncommunicable diseases, as reported by the WHO, which estimates 6.7 million premature deaths globally due to air pollution each year. This study aims to analyze the average PM2.5 levels for 2024–2025 in the Greater Surabaya Area and compare them with national quality standards from a public health perspective. This study employs a descriptive-analytical method using secondary data from the Directorate of Air Quality Pollution Control, incorporating spatial-temporal and comparative analyses based on the scope of monitoring days. The results show that Mojokerto Regency (49.4264 µg/m³), Sidoarjo Regency (34.2614 µg/m³), and Surabaya City (27.9185 µg/m³) in 2024 had higher levels compared to other areas. Meanwhile, in 2025, levels were higher in Sidoarjo Regency (29.6033 µg/m³) and Mojokerto Regency (19.3600 µg/m³). Several regions have concentration levels exceeding the national standard of 15 µg/m³. These findings indicate public health risks and the need for enhanced air quality monitoring and control of anthropogenic emissions to facilitate promotive-preventive interventions.